Ascertaining factors motivating use of digital libraries and formulating user requirements using Zachman framework - Abrizah, Abdullah; Zainab, Awang Ngah (Faculty of Computer Science and Information Technology, University of Malaya, 2006)
This paper describes the framework used in a study to formulate the requirements for the design and implementation of a collaborative digital library (CDL) for project-based learning. The CDL has been conceived to support secondary students information needs in conducting research projects. The study uses the Zachman Framework for Enterprise Architecture for the approach to investigate the initial requirements. The first artifact addressed in the framework - motivation (Why things are done) - is highlighted in this paper. Motivation in this work refers to major goals, curricular and programmes that are significant to the digital library relative to motivation. This includes the readiness to use the digital library, willingness to participate in content development and management, and the success factors. Using multiple data-gathering techniques, the study identifies the motivating factors that support the plan for realisation of the CDL. It outlines the vision statement, goals and objectives needed to define the strategic direction for the CDL project as perceived by the planner; the business plan or context to use the CDL as viewed by the owner; and the mandatory functional requirement of the digital library expressed as behavioural objectives as viewed by the designer.